New approaches to targeting the bone marrow microenvironment in multiple myeloma. (June 2016) - Gooding, Sarah; Edwards, Claire M
Highlights: Myeloma manipulates its bone marrow niche to better achieve its clonal proliferation. Niche-manipulation results in irreversible bone destruction and immune compromise. Drugs targeting tumour–niche interactions can improve bone disease and control tumour. Drugs such as PD-L1 inhibitors which target tumour immune-evasion are an important new tool. Abstract : Multiple myeloma is a tumour with a remarkably destructive effect on its host organ, the bone marrow. Through expression or secretion of adhesion molecules, growth factors, exosomes, miRNAs, chemokines and inhibitors, the tumour substantially alters its microenvironment, promoting both tumour survival and osteolytic bone disease. This altered niche is ideally suited to the sustenance of its proliferating compartment and the protection and immune evasion of its dormant, drug resistant fraction. The possibility of deepening response to a drug treatment regime, maintaining remission or even eradicating resistant stem cells by pharmacologically manipulating the tumour's interactions with this niche is a major driving force in current myeloma research. Examples of promising therapies include CXCR4 antagonists, RANKL inhibitors, HIF1α pathway inhibitors, and inhibitors of Notch, Wnt and TGFβ family pathways.